Digital-Based Village Administration Services Training in Madello Village - Ashariana; Fatmawati A. Mappasere; Indriati Amirullah; Tetty Dewiyanti; Nurkadarwati (www.amertainstitute.com, 2025)
Training and socialization of online-based administrative services in Paremono Village were carried out by involving village officials and heads using the Theory and Practice Approach method, Workshop and Simulation, Technical Assistance, Evaluation and Follow-up and Use of Learning Media. The purpose of this community service activity is to increase the knowledge of village officials and the community and improve administrative order in the Madello village office. The implementation of this PKM activity began with observation of partner needs, preparation of training materials, implementation of training and evaluation of activities. The participants of the activity were given training on how to access and use online-based village administration services using online application media in the form of Google Form, Google drive and Whatsapp. The results of this community service show that the level of understanding of village officials regarding digital-based village administration services increased from 67% to 78%.